2008
DOI: 10.4067/s0370-41062008000600006
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma en pediatría, experiencia en un hospital pediátrico

Abstract: Retinoblastoma in children, experience at a pediatric hospitalMethods: Retrospective analysis of clinical charts of 41 children (59 eyes) diagnosed with retinoblastoma and treated by a multidisciplinary team at Hospital Luis Calvo Mackenna in Santiago-Chile, between 1999 and 2007. The information included gender, laterality, diagnosis age, presenting signs, tumor spread, treatment modality and survival rate. Results: A total of 23 cases (56%) were unilateral and 18 cases (44%) were bilateral. The mean age at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Queremos mencionar que la medida de tendencia central utilizada por nosotros fue mediana y no promedio, principalmente por la distribución no homogénea de la muestra. Estos hallazgos hacen comparables nuestros números con los reportados en la literatura de países con mayor grado de desarrollo 2,8,[21][22][23] , y más altos que en reportes anteriores en Latinoamérica (80-94%) 4,8,24 . La supervivencia está asociada al estado de avance de la enfermedad 9 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Queremos mencionar que la medida de tendencia central utilizada por nosotros fue mediana y no promedio, principalmente por la distribución no homogénea de la muestra. Estos hallazgos hacen comparables nuestros números con los reportados en la literatura de países con mayor grado de desarrollo 2,8,[21][22][23] , y más altos que en reportes anteriores en Latinoamérica (80-94%) 4,8,24 . La supervivencia está asociada al estado de avance de la enfermedad 9 .…”
Section: Discussionunclassified
“…Su incidencia es cercana a 1 en 16.000 nacidos vivos 2 , aunque puede llegar hasta 1 en 34.000 3 . Se estima que en Chile hay 13 nuevos casos por año 4 . La mayoría de los casos se atiende bajo el sistema público, utilizando las Garantías Explícitas en Salud (GES).…”
Section: Introductionunclassified
“…4 In addition, said diagnostic influences therapeutic decisions, as some authors recommend that all germinal retinoblastoma patients should receive systemic chemotherapy to prevent the expression of new tumors and pineoblastoma. 1,3 In our country, survival is comparable to that of developed countries, 5,6 although mortality in Latin America remains close to 20%. 1,3 In our country, survival is comparable to that of developed countries, 5,6 although mortality in Latin America remains close to 20%.…”
Section: Introductionmentioning
confidence: 62%
“…Within each study, patient presentations were categorized according to a single presenting sign. Trincado et al (18) reported that 2 out of their group of 41 patients sought medical attention due to both leukocoria and strabismus; their cohort did not undergo orthoptic assessments.…”
Section: Discussionmentioning
confidence: 99%